Presurgical nasoalveolar moulding treatment in cleft lip and palate patients - Barry H. Grayson; Pradip R. Shetye (Indian Journal of Plastic Surgery)
Presurgical infant orthopedics has been employed since 1950 as an adjunctive neonatal therapy for the correction of cleft lip and palate. Most of these therapies did not address deformity of the nasal cartilage in unilateral and bilateral cleft lip and palate as well as the deficiency of the columella tissue in infants with bilateral cleft. The nasolaveolar molding (NAM) technique a new approach to presurgical infant orthopedics developed by Grayson reduces the severity of the initial cleft alveolar and nasal deformity. This enables the surgeon and the patient to enjoy the benefits associated with repair of a cleft deformity that is minimal in severity. This paper will discuss the appliance design, clinical management and biomechanical principles of nasolaveolar molding therapy. Long term studies on NAM therapy indicate better lip and nasal form, reduced oronasal fistula and labial deformities, 60 % reduction in the need for secondary alveolar bone grafting. No effect on growth of midface in sagittal and vertical plane has been recorded up to the age of 18 yrs. With proper training and clinical skills NAM has demonstrated tremendous benefit to the cleft patients as well as to the surgeon performing the repair.